PESAN MORAL DALAM FILM APEM KARYA SAMBA PICTURES ANALISIS WACANA KRITIS TEUN A. VAN DIJK - Galih Samudra, Hussein; Mulyana; Meilawati, Avi (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
The film "Apem" is A Javanese short film. Bringing the comedy drama genre with a touch of horror that depicts the social reality of rural communities. This film is interesting to study because exposes he main character’s inner problems, the dynamics of relationships between residents, and the existence of strong local myths and beliefs in Javanese culture. In this film there is also an ideological construction built by the screenwriter through the storyline and characterization. This study aims to uncover the moral message in the film "Apem" through text analysis, social cognition, and social context using a qualitative approach with Teun A. Van Dijk's Critical Discourse Analysis method. This approach focuses on the study of narrative structure, how the filmmaker constructs meaning, and the socio-cultural conditions surrounding the film's production and reception. This film depicts the spiritual journey of the character Mamad, a delinquent youth who experiences various mystical events until he finally realizes his mistakes and returns to the path blessed by God. The results of the analysis show that the moral message about the importance of repentance, self-introspection, and social responsibility is conveyed through character representation, visual symbolism, and the use of language.